PENGARUH UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 - Evander Leonard; Viriany Viriany (Jurnal Paradigma Akuntansi, 2026)
The aim of this research is to empirically show the effect of company size, and profitability, on the value LQ 45 companies listed on the Indonesia Stock Exchange (IDX). The population for this study is from 2019 using 135 data consisting of 45 companies. This research uses Eviews software version 12 to analyze the hypothesis. The results of this study indicate that profitability and firm size have a large and significant influence on firm value.